1961
DOI: 10.1103/physrev.121.1001
|View full text |Cite
|
Sign up to set email alerts
|

Defects in Irradiated Silicon. I. Electron Spin Resonance of the Si-ACenter

Abstract: The Si -A center is a major, radiation-damage defect produced in "pulled" silicon by a room temperature irradiation. As a result of studies described in this paper (I), and the following one (II), it is concluded that this center is a lattice vacancy with an oxygen atom impurity bridging two of the four broken bonds associated with the vacancy. Spin resonance and electrical activity arise from an electron trapped in the other two bonds. In this paper (I), the spin resonance studies are described. A molecular o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
219
1
8

Year Published

1963
1963
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 746 publications
(243 citation statements)
references
References 26 publications
15
219
1
8
Order By: Relevance
“…DLTS spectrum of an n-type FZ sample implanted with 1.4 ϫ10 8 /cm 2 B ͑6.8 MeV͒ ions at an angle of incidence of 7°relative to the surface normal. The rate window is ͑200 ms͒ Ϫ1 and the filling pulse duration is 50 ms. 18 with a large capture cross section (ϳ9ϫ10 Ϫ15 cm 2 ) while the second part ( p Ͼ10 Ϫ4 s) is related to the bistable C i C s pair 19 with a small apparent capture cross section (ϳ8 ϫ10 Ϫ18 cm 2 ). The configurational-coordinate energy diagram for the acceptor state of the C i C s pair, as determined by Song et al, 19 is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…DLTS spectrum of an n-type FZ sample implanted with 1.4 ϫ10 8 /cm 2 B ͑6.8 MeV͒ ions at an angle of incidence of 7°relative to the surface normal. The rate window is ͑200 ms͒ Ϫ1 and the filling pulse duration is 50 ms. 18 with a large capture cross section (ϳ9ϫ10 Ϫ15 cm 2 ) while the second part ( p Ͼ10 Ϫ4 s) is related to the bistable C i C s pair 19 with a small apparent capture cross section (ϳ8 ϫ10 Ϫ18 cm 2 ). The configurational-coordinate energy diagram for the acceptor state of the C i C s pair, as determined by Song et al, 19 is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The difference between the Ga i defects in the RTA and as-grown samples lies at their neighbouring atoms and geometric locations. By using a one-electron linear combination of atomic orbital scheme 26 and the charge density of the 4s electron ( ) 2 4 0 s ψ =72.7x10 24 cm -3 for a free neutral Ga atom 25,27 , the localization of the electron wave functions at the Ga i 2+ defects is estimated to be 20% (as-grown) and 16% (RTA). The rather strong localization shows that they are deep-level defects, a prerequisite for efficient carrier recombination.…”
Section: +mentioning
confidence: 99%
“…First of all, considerable interest is attracted to trapping of mobile vacancies at oxygen atoms resulting in formation of oxygen-vacancy pairs, the so-called A-centers as in the nomenclature of defects in irradiated Si [2,23]. These defects have been extensively studied by Hall effect measurements and DLTS spectroscopy; see for instance [24][25][26] and the literature contained therein.…”
Section: Role Of Oxygen In Defect Formation In Irradiated N-gementioning
confidence: 99%